What Young People Think About Music, Rhythm and Trauma: An Action Research Study - McFerran, Katrina; Crooke, Alex; Kalenderidis, Zoe; Stokes, Helen; Teggelove, Kate (Frontiers in Psychology, 2022)
A number of popular theories about trauma suggest rhythm has potential as a mechanism for regulating arousal levels, including Porge’s emphasis on regulating a hyper-vigilant amygdala (Polyvagal Theory, 2011) and van der Kolk’s (2015) focus on stimulating positive and reparative experiences through repetitive neural brainstem activity. However, there is very little literature examining this proposal from the perspective of the young people who might benefit. This action research project addresses this gap by collaborating with four groups of children in the out-of-home-care system to discover what they wanted from music therapists who bought a strong focus on rhythm-based activities. Four music therapy groups took place over 12 months and each cycle of action and reflection led to adjustments in what activities were offered, as well as exploring different levels of structure and ways of building relationships in the groups. The initial group incorporated a strong emphasis on highly structured rhythm-based activities, but young people found the format difficult to engage with. The second cycle included more opportunities for creativity and self-direction within semi-structured activities which children reported enjoying, but too much freedom also became overwhelming at times. The two groups in the third cycle seemed to balance structure and responsiveness successfully but were also influenced by the introduction of individual sessions prior to group commencement, which was designed to contribute to safety and trust building. Final reflections on the role of rhythm in supporting young people who have had adverse experiences are centred around co-regulation. This was qualitatively different to our expectations that practicing rhythm-based activities would lead to an expanded window of tolerance resulting in less time being spent in hypo-arousal or hyper-arousal. Instead of entraining to an external rhythm, young people felt safe when rhythms were matched, even if they were irregular, out-of-time and unpredictable. Small moments of co-regulation resulted in pleasure, comfort, satisfaction and peace and these moments were highly valued by the young people, who described just wanting to be relaxed and happy. Although not as rhythm-specific as literature might suggest, music making with trusted adults helped the young people in this study feel more content.